Pronomina Persona dalam Bahasa Dayak Benuaq di Kecamatan Muara Lawa Kabupaten Kutai Barat - Elkana April Lia; Widyatmike Gede Mulawarman; Asnan Hefni (Universitas Mulawarman, 2018)
This study aims to describe the pronoun of Dayak Benuaq language charm and its use in the community in Kecamatan Muara Lawa. In addition, this research is also a step to preserve one of Indonesia’s wealth of language, especially the Dayak language Benuaq. It is hoped that this research can explore and explore local wisdom values in the Dayak Benuaq community. The type of this research is descriptive qualitative research, that is research based on existing fact or phenomenon that empirically use Dayak Benuaq language. The technique of provision of data used is the technique of fishing rod, technique, skillful technique of advance, technological skill tansemuka, record recording technique. In the analysis of data used the method of agih or distributional, that is analyzing the language system or the whole rules that are set in the language based on the behavior or the characteristics of grammar on certain lingual units The results showed that the pronoun persona of the Dayak Benuaq language consists of three self-referential pronouns (1) the first single pronoun and the first plural pronoun consisting of ap, aqq, aweq, kaiq, and takaq, referring to the person to whom; (2) the pronouns of the second person singular and the pronouns of the second plural person consisting of aweq, ko, and ka, and referring to the person in question; (3) The third singular pronoun Persona and the third plural pronoun consisting of uhak, ongan, mali, and ulutn. The use of pronoun persona in Dayak Benuaq language is in accordance with the role of social factors (age, social status, and familiarity) on the use of pronouns persona, the use of pronouns persona in Dayak language Benuaq is adapted to the circumstances in communication, ie in terms of age, respected person or people who have a relationship of intimacy or kinship.